2015
DOI: 10.1159/000373965
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α- Mediated-p38-Dependent Signaling Pathway Contributes to Myocyte Apoptosis in Rats Subjected to Surgical Trauma

Abstract: Background: The accumulation of cytokines in the plasma after trauma can induce myocyte apoptosis. We aimed to identify which cytokine(s) present in the plasma responsible for myocyte apoptosis, and delineated the signal transduction mechanism in rats subjected to surgical trauma. Methods: Rats were randomized into two groups: control and trauma groups, which was divided into five subgroups: posttraumatic 0, 3, 6, 12, and 24 h subgroups. Cardiomyocytes isolated from traumatized rats were incubated with one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…P38α is originally identified as a protein kinase implicated in stress and inflammatory responses [3, 6, 8]. Activation of p38 MAPK is induced by the MAPK kinases MKK3 and MKK6.…”
Section: Introductionmentioning
confidence: 99%
“…P38α is originally identified as a protein kinase implicated in stress and inflammatory responses [3, 6, 8]. Activation of p38 MAPK is induced by the MAPK kinases MKK3 and MKK6.…”
Section: Introductionmentioning
confidence: 99%
“…The stimulation of PDCD4 induced the universal activation of NF-κB, as well as, the release of TNF-α and other inflammatory mediators that played a crucial role in the initiation and progression of CME-induced cardiac dysfunction. In addition, the increase in the level of TNF-α expression was one of the essential physiological responses of post-CME myocardial injury [14-17]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been found that mitogen-activated protein kinases (MAPKs) are important intracellular signal transduction systems that serve an important role in the development of inflammatory responses (19) induced by trauma (20), infection (21) and ischemia-reperfusion (22). The activation of the p38-MAPK pathway is important in cellular damage, including the production of proinflammatory cytokines, cytoskeletal remodeling and cellular apoptosis (23).…”
Section: Introductionmentioning
confidence: 99%